(untitled) (Jurnal Mu’allim, 2026)
This study employs a Systematic Literature Review (SLR) to identify and analyze various models and approaches to curriculum and learning innovation in Islamic Religious Education (IRE) during the period 2015–2025. The literature search and selection process was conducted rigorously through screening, filtering, and content analysis of 63 initial articles, resulting in 13 relevant and methodologically sound studies selected for in-depth review. The findings reveal that curriculum innovation in IRE involves diverse approaches, including design thinking, the integration of digital technology and artificial intelligence, and post-pandemic adaptations emphasizing flexibility, graduate competitiveness, and international recognition. These results highlight the importance of continuous innovation that addresses social, moral, and technological challenges in religious education while adapting to the dynamics of modernity and the digital era. The study recommends developing innovative, humanistic, and research-based models that integrate technology and collaboration to enhance the relevance and quality of IRE learning in the future.